Study on Okra (Abelmoschus esculentus L.) Response to Salt Stress Environment under Kabul Climatic Conditions, Afghanistan - Zafer Coşkun; Abdul Walid Salik; Mohammad Zaman Amini (Journal of Advanced Research in Natural and Applied Sciences)
Abstract − The research was conducted to examine the effects of saline-irrigation water on growth and fresh pod weight of okra (Abelmoschus esculentus L.) under climatic conditions of Kabul province, Af-ghanistan. This study consisted of four treatments having different salinity levels of irrigation water, (T1:0.0mM, T2:5mM, T3:10mM, and T4:20mM), which were applied throughout the growing season of okra in plastic pots with a randomized complete block design. Results showed that saline irrigation water caused a significant reduction in germination of seeds (in T1:98% germination, T4: 53% germination), leaf length (in T1:9.17 cm, T4:6.8cm leaf length), shoot height (in T1:15.43cm, T4: 13.87cm Shoot height) and root length (in T1:15.37cm, T4:8.7cm root length). Okra plants grown under salt stress conditions showed a significantly decline in yield as compared to control treatment. While 6904kg/ha yield was obtained in control treatment (T1), 6696kg/ha, 4772kg/ha, 3100kg/ha yield were obtained in T2, T3 and T4 applications, respectively. Water use efficiency was maximum in the control treatment and minimum in treatment level 20mM. A maximum value of 13.08kg/ha/mm was computed for control treatment and minimum value of 5.87kg/ha/mm for treatment level 20mM, the water use efficiency value for treatment level 5mM and 10mM were 12.68kg/ha/mm and 9.04kg/ha/mm respectively. As a result, okra growth parameters were decreased significantly with the increasing concentration of ECiw (electrical conductivity of irrigation water). Salinity adversely affected morphological and physiological characteristics of okra.